Neurocognitive profile of a cohort of SMA type 1 pediatric patients and emotional aspects, resilience and coping strategies of their caregivers. (March 2023) - Tosi, Michele; Cumbo, Francesca; Catteruccia, Michela; Carlesi, Adelina; Mizzoni, Irene; De Luca, Giacomo; Cherchi, Claudio; Cutrera, Renato; Bertini, Enrico; D'Amico, Adele
Abstract: Spinal muscular atrophy (SMA) type 1 represents the most severe condition of the spectrum of SMA 5q. In the absence of therapeutic interventions, patients do not achieve any motor milestone and their life expectancy does not exceed two years of age. To date, three disease-modifying drugs have been approved for SMA type I. These treatments have radically changed the natural history of the disease, improving motor, respiratory and bulbar functions. In recent years huge amount of data have been collected worldwide related to motor, respiratory and swallowing function outcome in treated patients, whereas the neurocognitive profile of treated patients has been poorly explored. Here we report the neurocognitive development profile of a cohort of SMA type I children treated with a disease modifying therapy. We also describe the burden and resilience as well as the coping strategies of their caregivers. Our finding show a global developmental delay in most patients and defects in gross motor functions contribute most to lower the general development quotient of Griffiths III, whereas the scores obtained on evaluating learning and language abilities scales suggest a positive trend in the developmental trajectory of general neurocognitive abilities. Some parents reported anxiety and stress but overall they were resilient (and had good coping strategies towards the burden of care for their child. These results reinforce the importance of routinely assessing the neurocognitive aspects in SMA type I patients and to offer an early intervention to favor the psychosocial development of these children. Highlights: Treatments approved for SMA have radically changed the natural history. The neurocognitive profile of treated patients has been poorly explored. We deeply investigated the neurocognitive profile and the emotionalburden of caregivers. Our finding show a global developmental delay. Positive trend of general neurocognitive abilities (language, learning).